2019
DOI: 10.12968/hmed.2019.80.9.517
|View full text |Cite
|
Sign up to set email alerts
|

Management of nocturia: overcoming the challenges of nocturnal polyuria

Abstract: Nocturia may be a multifactorial condition and should be regarded as a syndrome rather than a diagnosis, with many factors contributing to the clinical presentation. The effects of sleep deprivation can have a severely detrimental impact on the quality of life and productivity of the working age population, with considerable economic implications. Patients are unlikely to seek an appointment with their GP complaining of nocturia – they are more likely to complain of the effects of the condition, such as chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Currently, the medical application of dDAVP includes the treatment of central diabetes insipidus, primary nocturnal enuresis and nocturia [ 163 ]. Recently, it was shown that low dose desmopressin Noqdirna ® , as lyophilizate, is highly effective in treatments of nocturia due to idiopathic nocturnal polyuria in adults [ 164 ], same as MINIRIN ® MELT 1995 [ 165 ]. At much higher doses, dDAVP is used to treat coagulation disorders, such as hemophilia A and von Willebrand’s disease (VWD).…”
Section: Vasopressinmentioning
confidence: 99%
“…Currently, the medical application of dDAVP includes the treatment of central diabetes insipidus, primary nocturnal enuresis and nocturia [ 163 ]. Recently, it was shown that low dose desmopressin Noqdirna ® , as lyophilizate, is highly effective in treatments of nocturia due to idiopathic nocturnal polyuria in adults [ 164 ], same as MINIRIN ® MELT 1995 [ 165 ]. At much higher doses, dDAVP is used to treat coagulation disorders, such as hemophilia A and von Willebrand’s disease (VWD).…”
Section: Vasopressinmentioning
confidence: 99%